A novel Interactive Health Communication Application (IHCA) for parents of children with long-term conditions: Development, implementation and feasibility assessment. (2nd January 2016) - Swallow, Veronica; Carolan, Ian; Smith, Trish; Webb, Nicholas J. A.; Knafl, Kathleen; Santacroce, Sheila; Campbell, Malcolm; Harper-Jones, Melanie; Hanif, Noreen; Hall, Andrew
Abstract : Background : Few evidence-based, on-line resources exist to support home-based care of childhood long-term conditions. Methods : In a feasibility study, children with stages 3, 4, or 5 chronic kidney disease, parents and professionals collaboratively developed a novel Online Parent Information and Support (OPIS) application. Parents were randomized to an intervention arm with access to OPIS or a control arm without access. OPIS usage was assessed using Google Analytics. Parents in the intervention arm completed the Suitability Assessment of Materials (SAM) and User Interface Satisfaction (USE) questionnaires and participated in qualitative interviews. Results : Twenty parents accessed OPIS with a mean of 23.3 (SD 20.8, range 2–64) visits per user. Responses from the SAM and USE questionnaires were positive, most respondents rating OPIS highly and finding it easy to use. Qualitative suggestions include refinement of OPIS components, enabling personalization of OPIS functionalities and proactive endorsements of OPIS by professionals. Conclusions : Implementation of OPIS into standard practice is feasible in the centre where it was developed. Suggested developments will augment reported strengths to inform ongoing testing in the wider UK network of units. Our design and methods are transferrable to developing and evaluating web-applications to support home-based clinical care-giving for other long-term conditions.